Ký họa Việt Nam : đầu thế kỷ 20 = Vietnamese woodcuts at the beginning of the 20th century - Nguyễn, Mạnh Hùng, 1943-; Chinh Văn (Thành phố Hồ Chí Minh : Nhà Xuất Bản Trẻ, 1989)
Encyclopaedia of all the instruments, utensils of all the gestures of the life and crafts of the Tonkin Annamese people.
"A unique cultural treasure recently rediscovered after more than half a century in oblivion" -- Page 6.
Includes bibliographical references (pages [187]-[190])
Text in Vietnamese ; picture captions in Vietnamese with a parallel English translation.
Keywords: Wood-engraving, Vietnamese -- 20th century; Vietnamese -- Social life and customs